Magic on the menu: where are all the magical food and beverage experiences? - Spence, C; Youssef, J; Kuhn, G (MDPI, 2020)
Magic and dining have long been popular forms of entertainment. What is more, both involve some kind of transformation, and yet while the more theatrical aspects of dining have grown in popularity in recent decades, there is a surprising paucity of magical food and beverage experiences out there. In this article, we trace the historical appearance of food and drink and culinary items in the performance of magic. We also review some of the more magical elements of food design that have appeared on menus in bars and restaurants in recent years. We introduce the edible lightbulb dish from the menu at Kitchen Theory Chef’s Table and link it to the stage magic of Derren Brown. We also discuss some of the reasons as to why magical food experiences might be rare in the context of dining. In so doing, our hope is to highlight an intriguing area for future research and innovation. Along the way, we identify some possible candidate approaches for the introduction of edible magic onto the menu in the context of modernist cuisine.